A personal leadership statement (2025)
This leadership statement explores the concept of transformational leadership and"". its application in educational settings. We define transformational leadership and discuss the key assumptions of this leadership approach. Through the adoption of transformational leadership principles, educators can enable students to develop into critical thinkers, active learners, and confident individuals. The importance of collaborative work, critical thinking, and self-reflection in achieving educational goals is highlighted as well. By examining the implications of transformational leadership for future educators, we aim to shed light on the crucial role of leadership in shaping the future of education.